Relevance of Earnings and Cash Flow Information to Stock Prices on The Indonesia Stock Exchange - Vivaldy, Antonio; Adam, Kautsar (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the relevance of the value of profit and cash flow information to the stock price of companies listed on the Indonesia Stock Exchange (IDX). Profit and cash flow are two main indicators in assessing a company's performance, so it has the potential to influence investment decisions. The research uses secondary data in the form of financial statements and annual stock prices. The sample was selected through purposive sampling with the criteria of companies that consistently publish complete financial statements during the observation period. The analysis was carried out using multiple linear regression to test the influence of profit and cash flow on stock prices. The results show that earnings have a significant influence on stock prices, while cash flows show weak influence. This finding confirms that investors on the IDX are more focused on profit information in making investment decisions. This research contributes to the literature on value relevance and provides practical implications for companies in improving the quality of financial reporting.